(untitled) (Latakia University Journal -Medical Sciences Series, 2024)
Background : Pre-diabetes is a real warning sign of developing diabetes. The basic strategy to avoid the transition from pre-diabetes to type 2 diabetes lies in early detection of pre-diabetes to reduce the prevalence of diabetes and its huge economic burden Aim: The aim of this study was to determine the prevalence of pre-diabetes and undiagnosed diabetes among medical staff working at Tishreen University Hospital. Methods: A hospital-based cross-sectional study including 450 participants (230 female and 220 male), age 24 - 65 years surveyed. Type 2 diabetes and pre-diabetes were diagnosed by glycated hemoglobin A1c (HbA1c) levels(diabetes: HbA1c ≥6.5%; pre-diabetes: HbA1c ≥ 5.7% to <6.5%). Results and discussion: The results indicated that a vast majority of the evaluated healthcare personnel (360 people; 80%) had normal glycated hemoglobin levels. The remainder of the study group showed carbohydrate metabolism disturbances. Pre-diabetes was found in 85 people (18.9%) suggested an increased risk for diabetes. As a result of the study 5 people (1.1%) were diagnosed with diabetes (initial diagnosis). Conclusion: Screening of health care workers especially doctors having high risk of getting type 2 diabetes is reliable,effective and appropriate enough to be included in every hospital.